2020
DOI: 10.4103/1735-5362.301344
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin suppresses the growth and migration in HCT-116 human colorectal cancer cells by activating the p-38 MAPK signaling pathway

Abstract: Background and purpose: Crocetin is a natural antioxidant that is found in the crocus flower and Gardenia jasminoides (fruit). Previous studies have reported its anticancer activity both in vivo and in vitro . In addition, crocetin suppresses the growth and migration of human colorectal cancer cells, however, its mechanism of action remains to be elucidated. Therefore, the present study investigated the molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Saffron is a perennial herb of Crocus sativus (Iridaceae), which is not only a kind of spice but also a highly valued medicine (1,2). As a component of traditional medicine, saffron had been used as a medicinal herb for treating various ailments including cramps, asthma, liver disease, menstruation disorders, pain, and in the pathogenesis of cancer (3)(4)(5)(6)(7)(8). Crocin, crocetin, picrocrocin and safranal are the main secondary metabolites of Crocus sativus (9).…”
Section: Introductionmentioning
confidence: 99%
“…Saffron is a perennial herb of Crocus sativus (Iridaceae), which is not only a kind of spice but also a highly valued medicine (1,2). As a component of traditional medicine, saffron had been used as a medicinal herb for treating various ailments including cramps, asthma, liver disease, menstruation disorders, pain, and in the pathogenesis of cancer (3)(4)(5)(6)(7)(8). Crocin, crocetin, picrocrocin and safranal are the main secondary metabolites of Crocus sativus (9).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent in vitro study observed that crocin inhibits proliferation and migration of metastasis-associated in colon cancer 1 (MACC1)-expressing colorectal cells in a concentration dependent manner [123]. It is noteworthy that crocetin (800 μM) also represses growth and migration by the upregulation of p38 mitogen-activated protein kinase (MAPK) and downregulation of vascular endothelial growth factor (VEGF) and matrix metalloproteinase 9 (MMP-9) signaling pathways in HCT-116 human colorectal cancer cells [124] as well as Wnt/b-catenin (Wingless-type/b-catenin) pathway in mouse breast carcinoma cells [125]. In addition, the combination of saffron aqueous extract and high-intensity interval training (HIIT) strategy suppress tumor growth through the upregulation of p53 and Sirtuin-1 in breast cancer cells [117].…”
Section: Saffronmentioning
confidence: 99%
“…C Extracellular signal-regulated kinases (ERKs), are member of the mitogen-activated protein kinase (MAPK) involved in a series of physiological processes, such as the regulation of cell survival and proliferation as well as cell differentiation [44][45][46]. Colon tumor epithelial cells are dependent on mitogen activated protein kinase (MAPK) p38 for proliferation and survival [47,48]. We investigated the role of ERK and p38 in the observed antiproliferative effect.…”
Section: Mechanism Of Action Investigationmentioning
confidence: 99%